Development of a decision support system for evaluation of business process management systems - Cingil, İsmail. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
Owing to the fact that product assortment has been increased and product life cycle period has been decreased, surviving in this competitive market is not easy and may result in commercial failures for the organizations that cannot act against changes in a very short time. In order to overcome this dilemma, Business Process Management (BPM) systems are used by organizations. BPM system helps organizations to measure their processes and optimize their resources which increase their competence and intercept the idle operations that in turn decrease the decision period. There are many BPM products in the market and they all argue that they offer a complete BPM solution. However, implementing an Information System (IS) is costly and many of the implementations result in failure, therefore choosing the appropriate BPM system is important for the organizations. The purpose of this study is to help organizations to choose a proper BPM system for their business processes by developing a Decision Support System (DSS) by which they can evaluate and compare different BPM systems. The developed DSS is based on the three evaluation criteria groups; ISO/IEC 9126 Standards, Technical Criteria (Khan, 2004) and Marketing Criteria (Hill et. al., 2006) which are derived from literature survey, prior empirical studies and evaluation methods, series of observations, several brainstorming sessions and industry expert consultancy. Finally, two different BPM systems are evaluated by using the DSS Environment and the results are compared.
Keywords: Reengineering (Management); Business planning.; Decision support systems.; Management information systems.